Expo 86, Vancouver, B.C., Canada - World's largest Canadian Flag - Jurgen Vogt/Photo Graphics::::::::: (Agency Press)
The World's largest Canadian flag is located next to the Saskatchewan Pavilion at the entrance to the ALRT terminal taking people from the main fairsite to the Canada Pavilion. The flagpole is attached to the world's largest (62 meters) hockey stick.